Comodeling: From Requirements to an Integrated Software/Hardware Model. - Myers, Toby; Dromey, R. Geoff; Fritzson, Peter (Computer (00189162), 2011)
Comodeling lets developers systematically investigate and compare different software and hardware partitions to meet a system's constraints earlier in the design process, when integration problems are easier and cheaper to resolve.